2016
DOI: 10.5507/bp.2016.003
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1, S100 proteins and other RAGE ligands in cancer - markers, mediators and putative therapeutic targets

Abstract: Background and Aims. Activation of RAGE due to its increased expression in cancer cells or its stimulation by multiple ligands (AGEs, HMGB1, S100 proteins, etc.) may contribute to the proliferation, invasiveness of tumor cells and formation of distant metastases and also to the resistance of cancer to treatment. RAGE ligands could thus become both useful markers of disease severity and its outcome and, a potential therapeutic target. Conclusions. Better understanding of the role of RAGE activation in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 82 publications
2
15
0
4
Order By: Relevance
“…These findings make evident that RAGE-HMGB1 system is linked to aggressive breast cancer attitude representing a prognostic biomarker of remarkable clinical and therapeutic significance. Similar to our findings, several reports potentiate the link between RAGE and HMGB1 and the malignant virulence of cancer (Tesarova et al, 2016, Dhumale et al, 2015 (Kostova et al, 2010). Nankali et al, 2016 and his collegues, in their RT-PCR based study, found RAGE mRNA up-regulation in breast cancerous tissue that was significantly associated wih advanced-stage and triple-negative breast tumors, node-positive tissues and tumor size.…”
Section: ‫ـــــــــــــــــــــــــــــــــــــــــــــــــــــــــــsupporting
confidence: 92%
“…These findings make evident that RAGE-HMGB1 system is linked to aggressive breast cancer attitude representing a prognostic biomarker of remarkable clinical and therapeutic significance. Similar to our findings, several reports potentiate the link between RAGE and HMGB1 and the malignant virulence of cancer (Tesarova et al, 2016, Dhumale et al, 2015 (Kostova et al, 2010). Nankali et al, 2016 and his collegues, in their RT-PCR based study, found RAGE mRNA up-regulation in breast cancerous tissue that was significantly associated wih advanced-stage and triple-negative breast tumors, node-positive tissues and tumor size.…”
Section: ‫ـــــــــــــــــــــــــــــــــــــــــــــــــــــــــــsupporting
confidence: 92%
“…The localization of both proteins turned out to be closely related to autophagy, which suggested that the relationship between HMGB1 and p53 may regulate the balance between tumour cell death and survival. A possible mediator may be RAGE (Receptor for Advanced Glycation End products), which is a specific cellular receptor for HMGB1 [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…Ligand formation not only initiates intracellular signal transduction but also upregulates RAGE expression 29 . The interactions of RAGE with various ligands have crucial roles in cancer pathogenesis and progression 30 , through cell proliferation and invasion occur 31 . The binding of RAGE with S100A9 is essential in cervical cancer development 32 .…”
Section: Discussionmentioning
confidence: 99%